Financial Reform : What Shakes It? What Shapes It? - Mody, Ashoka; Abiad, Abdul (Washington, D.C. : International Monetary Fund, 2005)
Financial sector liberalization was high on the agenda of policymakers during the last quarter of the twentieth century. But there were significant differences in the pace and scale of reform. This pamphlet examines the factors triggering-or impeding and even reversing-financial reform in 35 economies, both industrial and developing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Country; EI; Government; Liberalization; Reform; New Zealand